2015
DOI: 10.5603/fm.2015.0120
|View full text |Cite
|
Sign up to set email alerts
|

Ring-shaped variation of the coeliac trunk branches

Abstract: Aberrant arterial variations in the branching (Folia Morphol 2015; 74, 4: 540-543)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Anatomical variations of the CeT and CHA which have various classifications have been documented and classified several times in the available literature with MDCT angiography, digital subtraction angiography or cadaveric dissections [17,19,23]. CeT and CHA with normal anatomy were seen in most of the previous studies; however, some authors reported a number of variations.…”
Section: Resultsmentioning
confidence: 99%
“…Anatomical variations of the CeT and CHA which have various classifications have been documented and classified several times in the available literature with MDCT angiography, digital subtraction angiography or cadaveric dissections [17,19,23]. CeT and CHA with normal anatomy were seen in most of the previous studies; however, some authors reported a number of variations.…”
Section: Resultsmentioning
confidence: 99%